Integrative analysis of different low-light-tolerant watermelon lines in response to low-light stress - Xiaojing Ma; Yong Wang; Xiaohui Li; Yongpeng Liu; Hengbin Luo; Wenkai Shang; Yancui Di; Ningning Gao; Liyun Kang; Fengzhi Piao; Zhixin Guo; Han Dong; et al. (BMC Plant Biology)
Abstract Low-light stress is a major environmental factor limiting watermelon growth and productivity; however, the molecular and physiological mechanisms underlying low-light tolerance remain unclear. In this study, we compared the morphological, physiological, biochemical, and transcriptomic responses of two watermelon inbred lines, HY25 (low-light tolerant) and DQ22 (low-light sensitive), under low-light conditions (60 µmol m⁻² s⁻¹) and normal light (200 µmol m⁻² s⁻¹). Morphological assessments revealed that low-light stress considerably inhibited shoot and root development in both lines, with DQ22 exhibiting more severe reductions in plant height, biomass, and root architecture. Photosynthetic analysis revealed that, compared with HY25, DQ22 resulted in greater decreases in the net photosynthetic rate, stomatal conductance, transpiration rate, chlorophyll content, and PSII efficiency (Fv/Fm). Biochemical assays showed that DQ22 resulted in increased levels of reactive oxygen species (ROS), malondialdehyde (MDA), and relative electrolyte leakage (REL), whereas HY25 maintained increased antioxidant enzyme activity and decreased cellular damage. Additionally, HY25 resulted in greater retention of carbohydrate and protein contents under stress. Transcriptome analysis revealed 8,291 differentially expressed genes (DEGs), with HY25 exhibiting increased expression of genes related to photosynthesis, carbohydrate metabolism, and ROS detoxification. Notably, genes involved in light-harvesting complexes, carbon fixation, and porphyrin metabolism were more actively expressed in HY25. Moreover, auxin-related genes presented genotype-specific expression under stress. These findings clarify key physiological traits and gene regulatory mechanisms associated with low-light tolerance in watermelon and provide valuable insights for developing stress-resistant cultivars.